Computed Tomography of the Head and Neck Region for Tumor Staging—Comparison of Dual-Source, Dual-Energy and Low-Kilovolt, Single-Energy Acquisitions. Issue 9 (September 2017) - May, Matthias Stefan; Bruegel, Joscha; Brand, Michael; Wiesmueller, Marco; Krauss, Bernhard; Allmendinger, Thomas; Uder, Michael; Wuest, Wolfgang
Abstract : Purpose: The aim of this study was to intra-individually compare the image quality obtained by dual-source, dual-energy (DSDE) computed tomography (CT) examinations and different virtual monoenergetic reconstructions to a low single-energy (SE) scan. Materials and Methods: Third-generation DSDE-CT was performed in 49 patients with histologically proven malignant disease of the head and neck region. Weighted average images (WAIs) and virtual monoenergetic images (VMIs) for low (40 and 60 keV) and high (120 and 190 keV) energies were reconstructed. A second scan aligned to the jaw, covering the oral cavity, was performed for every patient to reduce artifacts caused by dental hardware using a SE-CT protocol with 70-kV tube voltages and matching radiation dose settings. Objective image quality was evaluated by calculating contrast-to-noise ratios. Subjective image quality was evaluated by experienced radiologists. Results: Highest contrast-to-noise ratios for vessel and tumor attenuation were obtained in 40-keV VMI (all P < 0.05). Comparable objective results were found in 60-keV VMI, WAI, and the 70-kV SE examinations. Overall subjective image quality was also highest for 40-keV, but differences to 60-keV VMI, WAI, and 70-kV SE were nonsignificant (all P > 0.05). High kiloelectron volt VMIs reduce metal artifacts with only limited diagnostic impact because of insufficiency in case of severe dental hardware. CTDIvol did not differ significantly between both examination protocols (DSDE: 18.6 mGy; 70-kV SE: 19.4 mGy; P = 0.10). Conclusions: High overall image quality for tumor delineation in head and neck imaging were obtained with 40-keV VMI. However, 70-kV SE examinations are an alternative and modified projections aligned to the jaw are recommended in case of severe artifacts caused by dental hardware.